Implementasi Efek Warp Stabilizer dalam Pembuatan Video Profil Program Studi Teknik Mesin - Muhazzar, Rifki; Prasetyaningsih, Sandi (Politeknik Negeri Batam, 2024)
The instability of video recordings is a common issue that often occurs during recording, especially when using limited equipment or in uncontrolled situations. This problem can become serious when it is not possible to re-record. Therefore, a solution is needed at the video editing stage. One existing solution is using the warp stabilizer effect in Adobe Premiere Pro. Based on research conducted on the profile video of the Mechanical Engineering Study Program, there were 8 recordings that experienced this issue according to the profile video creators. Alpha testing resulted in 6 video recordings being categorized as unstable. Then, beta testing yielded 95.33% in the unstable category, 89.37% in the very unstable category, and 91.36% overall, which means that the implementation of the warp stabilizer is very effective in reducing instability, making the profile video of the Mechanical Engineering Study Program more professional.